Video Marketing: Best Practices and Simple Tips for Libraries - Robin O'Hanlon; Heather A. Dalal; Karen L. Yacobucci (Marketing Libraries Journal, 2017)
Many information professionals have experimented with creating video content for instructional purposes. Video marketing is another mode of video communication that can appeal to and engage library users. In this article, the authors of a forthcoming book on video marketing for librarians share best practices, along with practical tips for video marketing production. Tips include specific information on topics such as message development, preproduction, video equipment, postproduction including editing, as well as accessibility and discoverability. Alternatives to traditional live-action video, including online animation, are also explored.